Karakteristik Agronomis dan Fisikokimia Umbi Klon Ubikayu Genjah - Sundari, Titik; Yulifianti, Rahmi (Jurnal Penelitian Pertanian Tanaman Pangan, 2011)
The research was aimed to characterize agronomic characters and physico-chemical tubers of early maturating cassava clones. Total of 10 cassava clones and five varieties (UJ 3, UJ 5, Adira 1, Adira 4 and Malang 6) were evaluated in two locations, namely at the experiment station of Muneng, Probolinggo and at farmer’s land in South Malang. The experiment was planted in April to November 2009, using a completely randomized block design with three replications. Each clone was planted in plots measuring 5 m x 4 m with plant spacing of 100 cm x 80 cm. Fertilization was applied in three stages by using 10 t/ha of manure and 200 kg urea + 100 kg SP36 + 100 kg KCl/ha. Manure was given at the time of land preparation, while urea, SP36, and KCl were given at one month after planting (MAP) (100 kg of urea, 50 kg of KCl, 100 kg of SP36/ha), and three MAP (100 kg of urea and 50 kg of KCl/ha). Observations on the agronomic characters included: plant height, number of fresh leaves, number of node and diameter of stem conducted at 3 WAP until the harvest, at intervals of 1 month. Yield and yield components, and physical-chemical characters of tuber were measured at harvest. Combined analyses of two locations showed that the interaction between clones and locations were significant on all observed agronomic characters. OMM 9076 clone was consistently out yielded at two locations. Based on physicochemical characters, CMM 03001-10, CMM 03094-12, CMM 03009-6, CMM 03097-11, CMM 03013-11, CMM 03094-13, CMM 03018-10, M4-p, OMM 9076 and Adira 1 clones were considered suitable for food. Clone M4p was also suitable for starch or flour industries, and CMM 03013-11 was suitable for ethanol.